Inside Back Cover: A Green Strategy to Enhance a Liquid–Liquid Heterogeneous Reaction with a Magnetic Recyclable Pickering Emulsion (ChemCatChem 4/2015). Issue 4 (February 2015) - Feng, Linbin; Wang, Jianli; Chen, Liang; Lu, Meizhen; Zheng, Zhi; Jing, Ren; Chen, Hualiang; Shen, Xianbo
<x xml:space="preserve">Abstract</x> The cover picture shows a general strategy to improve the reaction of a typical organic–aqueous heterogeneous green oxidation system, in which surface properties and tunable magnetic nanoparticles were introduced to form a controllable and well‐dispersed emulsion. In their Full Paper, L. Feng et al. reveal that the addition of nanoparticles with proper surface modification can result in improved Montanari reactions compared with the conventional reaction system. The article highlighted by this cover can be found on p. 616 ff. of Issue 4, 2015.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>